2017
DOI: 10.21037/gs.2017.09.12
|View full text |Cite
|
Sign up to set email alerts
|

Near total parathyroidectomy for the treatment of renal hyperparathyroidism

Abstract: ntPTX is associated to very satisfying rates of normal parathyroid function and of relapse of hyperparathyroidism (6.4%) at long term, either in case of RTx or of maintenance hemodialysis: the concept of "small amount" remnant represents a valuable choice for patients undergoing PTX with a realistic chance of receiving a RTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…There is the potential for late graft failure, possibly due to scar maturation causing local ischemia 272,297. Conversely, the grafts can become hyperplastic with time and can infiltrate into surrounding structures and blood vessels 272,307. In addition, THPT can develop at the site of an autograft after kidney transplantation due to the persistence of nodular tissue in the autograft 308.…”
Section: Planning Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…There is the potential for late graft failure, possibly due to scar maturation causing local ischemia 272,297. Conversely, the grafts can become hyperplastic with time and can infiltrate into surrounding structures and blood vessels 272,307. In addition, THPT can develop at the site of an autograft after kidney transplantation due to the persistence of nodular tissue in the autograft 308.…”
Section: Planning Of Surgerymentioning
confidence: 99%
“…264,265,270 There is no consensus on the size of the remnant left behind; various studies have described remnants weighing 30 to 50 mg, 40 to 50 mg or 40 to 80 mg, or measuring 1/3 to 1/2 the gland, half the size of a normal gland, 2 to 3 times the size of a normal gland, or a 3 × 3 × 3 mm remnant. 264,265,[267][268][269]271,272 Once the remnant is marked and examined for viability, the remaining glands can be excised. 166 Upon closing, some surgeons mark the level of the remnant with a non-absorbable suture in the strap muscles.…”
Section: Subtotal Ptxmentioning
confidence: 99%
“… 17 showed that patients who had the most prominent reduction in serum calcium were those with the highest baseline concentrations of PTH and alkaline phosphatase. Higher baseline PTH concentrations also have been associated with a higher risk of sustained hypocalcemia and higher needs for calcium supplementation after parathyroidectomy 15, 16, 18, 19, 20. Collectively, these data suggest that patients with more severe sHPT should be monitored most closely for calcimimetic-induced hypocalcemia.…”
Section: Resultsmentioning
confidence: 90%
“…Higher baseline PTH concentrations also have been associated with a higher risk of sustained hypocalcemia and higher needs for calcium supplementation after parathyroidectomy. 15,16,[18][19][20] Collectively, these data suggest that patients with more severe sHPT should be monitored most closely for calcimimetic-induced hypocalcemia.…”
Section: Discussionmentioning
confidence: 90%